Synergetic effect of chitosan and vitamin C on the oxidative enzyme status in rat exposed to lead acetate - Aditya Marianti; Fransisca Widhi Mahatmanti (Acta Scientiarum. Biological Sciences, 2018)
This article discusses the research results on the synergetic effect of chitosan and vitamin C in overcoming free radical effect due to blood lead (Pb2+) accumulation. Blood lead level and enzymatic activities of superoxide dismutase (SOD), catalase oxidase (CAT), and Glutathione peroxidase (GPx) were used as the main parameters. Thirty adult male albino rats were divided into six groups. Group 1 was normal control group; group 2 was the negative control group treated with lead acetate at 175 mg kg-1 body weight (BW). Group 3 was treated with 64 mg kg-1 BW of chitosan day-1. Group 4, 5, and 6 were treated with chitosan and vitamin C combination at the dose of 100, 200, and 300 mg kg-1 BW, respectively. All groups were inducted using 175 mg kg-1 BW of Pb-acetate, excluding control group. Results showed that chitosan and vitamin C treatment at the dose of 300 mg kg-1 BW decreased blood Pb2+ level in rats exposed to Pb-acetate. The combination also significantly increased enzymatic activities from SOD, CAT, and GPx compared to the other groups. In conclusion, the combination of chitosan and vitamin C could elevate the several antioxidative enzymes activities in Pb-acetate induced rats.